Factors That Affect Stock Returns in Food and Beverage Companies Listed on the Indonesian Stock Exchange - Wahyu Indah Mursalini; Esi Sriyanti; Attila Nurhida Putri (Transpublika Publisher, 2025)
The primary objective of this research is to analyze the financial progress of Food and Beverage Companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The study focuses on four main parameters: Economic Value Added (EVA), Market Value Added (MVA), Refined Economic Value Added (REVA), and Financial Value Added (FVA), and their influence on stock returns. The research methodology employed is quantitative. The target population consists of all Food and Beverage Companies listed on the Indonesia Stock Exchange during the specified period. A purposive sampling method was used to select 20 samples that met specific criteria. Data were collected from secondary sources, specifically annual reports. Data analysis was conducted using SPSS 25 software to assess the influence of EVA (X1), MVA (X2), REVA (X3), and FVA (X4) on stock returns. The results of the study indicate that EVA (X1) and MVA (X2) do not significantly impact stock returns, with t-values of -0.266 and 1.485, respectively. Similarly, REVA (X3) does not show a significant effect on stock returns, with a t-value of 0.643. However, FVA (X4) demonstrates a significant negative relationship with stock returns, with a t-value of -2.423. When considered collectively, EVA, MVA, REVA, and FVA do not have a significant effect on stock returns. The F-value was 1.738, with a significance level of 0.153.